Effects of Na and MoS2 on Cu2ZnSnS4 thin‐film solar cell. (26th April 2014) - Yang, Kee‐Jeong; Sim, Jun‐Hyoung; Jeon, Boram; Son, Dae‐Ho; Kim, Dae‐Hwan; Sung, Shi‐Joon; Hwang, Dae‐Kue; Song, Soomin; Khadka, Dhruba B.; Kim, JunHo; Kang, Jin‐Kyu
Abstract Cu2ZnSnS4 (CZTS)‐based materials have a useful band gap and a high absorption coefficient; however, their power conversion efficiency is low compared with that of CdTe and Cu(In, Ga)Se2‐based solar cells. Two of the factors that strongly affect CZTS solar cell characteristics are the MoS2 layer and the presence of defects. In this study, Mo back‐contact layers were annealed to control MoS2 layer formation and the Na content in the Mo layer before the absorber precursor layer was deposited. The increase in oxygen content in the Mo layer suppressed MoS2 layer formation. In addition, the increase in Na diffusion during the initial stage of the absorber precursor deposition decreased the defect density in the absorber layer and in the absorber–buffer interface. These results were verified through measurements of the external quantum efficiency, the temperature dependence of the open‐circuit voltage (VOC), and admittance spectra. The current densities (JSC) and VOC, as well as the power conversion efficiencies, improved as the annealing temperature of the Mo layer increased, which suggests that CZTS solar cell characteristics can be improved by suppressing MoS2 layer formation and increasing Na content in the Mo layer before deposition of the absorber precursor layer. Copyright © 2014 John Wiley & Sons, Ltd.